2010
DOI: 10.1074/jbc.m110.105189
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Mycobacterium tuberculosis β-Ketoacyl-Acyl Carrier Protein Reductase MabA Regulates Mycolic Acid Biosynthesis

Abstract: Mycolic acids are key cell wall components for the survival, pathogenicity, and antibiotic resistance of the human tubercle bacillus. Although it was thought that Mycobacterium tuberculosis tightly regulates their production to adapt to prevailing environmental conditions, the molecular mechanisms governing mycolic acid biosynthesis remained extremely obscure. Meromycolic acids, the direct precursors of mycolic acids, are synthesized by a type II fatty acid synthase from acyl carrier protein-bound substrates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
64
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 60 publications
2
64
0
Order By: Relevance
“…The MS/MS spectra unambiguously identified the presence of two phosphate groups on peptide(14 -30) ( Fig. 2A) and peptide (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) (Fig. 2B), thus indicating that CcpA is phosphorylated on two threonines, corresponding to Thr-18 and Thr-33.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MS/MS spectra unambiguously identified the presence of two phosphate groups on peptide(14 -30) ( Fig. 2A) and peptide (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) (Fig. 2B), thus indicating that CcpA is phosphorylated on two threonines, corresponding to Thr-18 and Thr-33.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of Complementation with the CcpA Phosphomimetic Mutant in ⌬ccpA Mutant Strain-Acidic residues such as aspartic acid (Asp) qualitatively mimic the phosphorylation effect with regard to functional activity (24,34,36,38,40,41). Therefore, phosphoablative (Thr to Ala replacements) and phosphomimetic (Thr to Asp replacements) ccpA alleles were generated and cloned into the E. coli-S. aureus shuttle plasmid pCN34 under the control of the ccpA promoter to trans-complement the S. aureus SA113 ⌬ccpA mutant KS66 (12).…”
Section: Resultsmentioning
confidence: 99%
“…Signaling through STPKs has recently emerged as a key regulatory mechanism in M. tuberculosis, playing roles in the transport of metabolites (22), cell division (23), and virulence (24). Several metabolic pathways such as mycolic acid (25)(26)(27)(28), glutamine (29), phthiocerol dimycocerosates (30), and glucan (31) biosyntheses have been shown to be regulated by M. tuberculosis STPK phosphorylation.…”
mentioning
confidence: 99%
“…To identify the number and nature of the phosphorylation sites, we opted for a mass spectrometry (MS) analysis, which was successfully developed previously (6,11,23,24). To this aim, LuxS was incubated with cold ATP in the presence of Stk1 and subjected to mass spectrometry analysis after tryptic digestion.…”
mentioning
confidence: 99%
“…As revealed by the mapping on the LuxS structure, the Thr14 site appears critical for LuxS enzymatic activity. Therefore, following a strategy that has been successfully used to demonstrate that regulation of a substrate protein via phosphorylation is important during active cell growth in mycobacteria (Wag31) (12) or for mycolic acid metabolism (mtFabH or MabA) (23,24), we generated the phosphorylation mimic LuxS_T14D by site-directed mutagenesis (Tables 1 and 2) and expressed and purified it. Previous studies have shown that acidic residues such as Asp or Glu qualitatively recapitulate the effect of phosphorylation with regard to functional activity (12,23,24).…”
mentioning
confidence: 99%